2006
DOI: 10.1002/pip.690
|View full text |Cite
|
Sign up to set email alerts
|

Chemical natures and distributions of metal impurities in multicrystalline silicon materials

Abstract: We present a comprehensive summary of our observations of metal-rich particles in multicrystalline silicon (mc-Si) solar cell materials from multiple vendors, including directionally-solidified ingot-grown, sheet, and ribbon, as well as multicrystalline float zone materials contaminated during growth. In each material, the elemental nature, chemical states, and distributions of metal-rich particles are assessed by synchrotron-based analytical x-ray microprobe techniques. Certain universal physical principles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
115
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 80 publications
5
115
2
Order By: Relevance
“…To explain these phenomena, we have used appropriate equilibrium phase diagrams ( Figure 1 a and Figure 3 c ). The precipitation pathway proposed herein may help explain previous reports [24][25][26][27][28][29] of mixed-metal silicide precipitates in silicon that can exhibit the same nanoscale spatial segregation into Cu-rich and Ni-rich silicide phases evident in Figure 3 . It is proposed that these precipitates observed in as-grown mc-Si may form via decomposition of homogeneous liquid metal-silicon alloy droplets either incorporated during crystallization or precipitated during cooldown.…”
supporting
confidence: 81%
“…To explain these phenomena, we have used appropriate equilibrium phase diagrams ( Figure 1 a and Figure 3 c ). The precipitation pathway proposed herein may help explain previous reports [24][25][26][27][28][29] of mixed-metal silicide precipitates in silicon that can exhibit the same nanoscale spatial segregation into Cu-rich and Ni-rich silicide phases evident in Figure 3 . It is proposed that these precipitates observed in as-grown mc-Si may form via decomposition of homogeneous liquid metal-silicon alloy droplets either incorporated during crystallization or precipitated during cooldown.…”
supporting
confidence: 81%
“…Preferentially, precipitation of impurities occurs at dislocations and other crystal imperfections. 25 Investigating the impact of metal impurities and precipitates on the reverse current-voltage characteristic of p-n junctions, Goetzberger and Shockley 4 identified localized current paths through junctions that were treated in a manner expected to produce metal precipitates. The result of the precipitation treatment was a "softening" of the reverse characteristic due to excess currents below AB.…”
Section: A Light Emission From Reverse-biased P-n Junctionsmentioning
confidence: 99%
“…When metal impurities conglomerate to form large precipitates at grain boundaries and dislocations in Si wafers, the precipitated impurities usually have low recombination activity. In contrast, the recombination activity of the metal impurities would be high enough to reduce the minority carrier diffusion length to less than 1 μm if the impurities with high concentrations were in interstitial or substitutional sites [13][14][15]. It can be concluded that the properties of Si wafers and the resulting performance of solar cells not only depends on the total concentrations of impurities, but also on the structure, chemical state and spatial distribution of the impurities in the Si wafers.…”
Section: Influence On Electrical Propertiesmentioning
confidence: 99%